2015
DOI: 10.1007/jhep06(2015)153
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational radiation in massless-particle collisions

Abstract: Abstract:The angular and frequency characteristics of the gravitational radiation emitted in collisions of massless particles is studied perturbatively in the context of classical General Relativity for small values of the ratio α ≡ 2r S /b of the Schwarzschild radius over the impact parameter. The particles are described with their trajectories, while the contribution of the leading nonlinear terms of the gravitational action is also taken into account. The old quantum results are reproduced in the zero frequ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…At low-enough energy the spectrum reproduces the expected (finite) ZFL. But its shape above ω ∼ b −1 is universal and tuned on R −1 , deviating from the ZFL by a power of ω above ω ∼ R −1 in agreement with recent classical results [15,16]. Because of the role of R −1 , the characteristic frequency/energy of the emitted gravitons decreases when the energy of the collision is increased above the Planck scale.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…At low-enough energy the spectrum reproduces the expected (finite) ZFL. But its shape above ω ∼ b −1 is universal and tuned on R −1 , deviating from the ZFL by a power of ω above ω ∼ R −1 in agreement with recent classical results [15,16]. Because of the role of R −1 , the characteristic frequency/energy of the emitted gravitons decreases when the energy of the collision is increased above the Planck scale.…”
supporting
confidence: 87%
“…The purpose of this note is to go beyond the analysis of [9,10] and to show that the graviton's spin 2, besides making it possible for an effective metric to emerge, also determines the detailed form of graviton bremsstrahlung in a whole frequency and angular range, covering in particular the forward fragmentation regions responsible for the excessive energy emission. As we will show, taking properly into account coherence effects not only solves the energy-conservation issue, but also leads to a gravitons spectrum with characteristic energies of order R −1 , the typical energy of Hawking's radiation out of a black hole of mass E. The main features of such a picture are consistent with their classical counterparts recently discussed in [15,16]. In this short note we will sketch the derivation and present the main physical results leaving most of the technical details to a forthcoming paper [17].…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Pavel Spirin discussed an analysis 45 on the angular and frequency characteristics of the gravitational radiation emitted in collisions of massless particles in the context of classical GR for small values of the Schwarzschild radius to impact parameter ratio, α. He presented a comparison with previous results in the literature and showed that the radiation efficiency outside a narrow cone of angle α in the forward and backward directions with respect to the initial particle trajectories is ∼ α 2 .…”
Section: Collisions and Collapsementioning
confidence: 99%